2016
DOI: 10.5539/ijel.v6n4p213
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Metacognitive Teaching Strategies to Enhance Elementary School Pupils’ Reading Skills in the Northern Border Areas of Saudi Arabia

Abstract: Difficulties in the fields of learning are among the most modern special educational fields and the fastest developing because of the extra concern from the parents and those concerned with children who show learning disorders, which cannot be explained by mental, physical or working disorders. Learning metacognition has short term benefits in the field of learning and teaching as it gives the individual the ability to connect between their learning successes to themselves. It increases their confidence with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The study was applied to a sample of 65 students in elementary levels, who were assigned to two groups; 35 each. After applying the metacognitive strategy on the experimental group, the study revealed significant results in the improvements of skills among students with learning disabilities and thus support the use of such strategies in education (Alenizi & Alanazi, 2016). Also in Saudi Arabia, another study examined the improvement of reading comprehension among deaf and hard of hearing (DHH) in higher education by using metacognitive strategies that use digital books.…”
Section: Previous Studiesmentioning
confidence: 82%
“…The study was applied to a sample of 65 students in elementary levels, who were assigned to two groups; 35 each. After applying the metacognitive strategy on the experimental group, the study revealed significant results in the improvements of skills among students with learning disabilities and thus support the use of such strategies in education (Alenizi & Alanazi, 2016). Also in Saudi Arabia, another study examined the improvement of reading comprehension among deaf and hard of hearing (DHH) in higher education by using metacognitive strategies that use digital books.…”
Section: Previous Studiesmentioning
confidence: 82%
“…This indicates that male and female teachers are more ware of students' behavioral traits as a results of teaching scientific subjects. Table (3) shows that there are statistically significant differences between the averages of the demographic variable (i.e., years of experience) between male and female teachers regarding the accuracy of their nomination of male and female students based on the scores of students on four dimensions of behavioral traits scale and the overall score, and this was in favor of years of experience arranged (5:10) years. This result implied that teachers with less than five years of experience are not sufficiently prepared to provide adequate identification of gifted students.…”
Section: Participant Sample and Data Sourcementioning
confidence: 99%
“…There has been an increasing amount of research attention given to the importance of teacher nominations as a major criteria for identifying gifted students in Saudi Arabian schools (Alenizi & Shaaban, 2023;Alnafie et al 2000). On the other hand, most of such research examined teacher nominations of gifted students' behavioral characteristic for the purpose of gifted program eligibility, not for the purpose of In general, gifted education in Saudi Arabia follows the traditional system of gifted programming, which involves the definition of gifted students, screening and identification process to identify and nominate such students for special provisions.…”
Section: Introductionmentioning
confidence: 99%
“…Reading among EFL students is not an easy task. For overcoming the reading difficulties Alenizi and Alanazi (2016) tried to increase EFL students' confidence and to create opportunities to let them to develop their reading skills through metacognitive skills. Maasum and Maarof (2012) studied the effectiveness of explicating strategic reading and monitoring to overcome reading comprehension difficulties among EFL learners.…”
Section: Reading Comprehension Difficultiesmentioning
confidence: 99%